PENGEMBANGAN INOVASI PEMBELAJARAN ISLAMI MELALUI IMPLEMENTASI KURIKULUM MERDEKA DI PAUD AL IRSYAD AL ISLAMIYYAH - sholeh, muh ibnu sholeh (Jurnal I TIBAR, 2025)
Early Childhood Islamic Education (PIAUD) plays a crucial role in shaping children's foundation of faith, morals, and intellect from an early age. The Kurikulum Merdeka, which provides flexibility in curriculum design and a student-centered approach, presents an opportunity to integrate Islamic values into learning. This study aims to analyze the development of Islamic learning innovations through the implementation of Kurikulum Merdeka at PAUD Al Irsyad Al Islamiyyah Tulungagung. Using a qualitative approach with a case study method, this research explores the application of an Islamic values-based Kurikulum Merdeka in learning activities at PAUD Al Irsyad Al Islamiyyah Tulungagung. The findings reveal that PAUD Al Irsyad Al Islamiyyah has successfully developed various Islamic learning innovations, such as Prophet-based storytelling, the "Knowing Allah’s Creations" project, and the use of enjoyable and creative thematic approaches. This learning approach not only enhances children's cognitive skills but also fosters their social, emotional, and spiritual character development in accordance with Islamic educational principles. However, several challenges remain, including limited teacher competence in implementing Kurikulum Merdeka, a lack of supporting digital learning facilities, and insufficient parental involvement in supporting children's education at home. This study provides recommendations for strengthening teacher training, improving learning facilities, and enhancing partnerships with parents. These findings can serve as a model for other Islamic educational institutions in implementing a contextual curriculum based on Islamic values to holistically develop children's potential.